Exergoeconomic and environmental impact assessment of a semi-scale office with solar chimney and evaporative cooling tower for sustainable space cooling and air ventilation - Bashar Shboul; Mohamed E. Zayed; A.S. Abdelrazik; Mohammad Alrbai; Alhaj-Saleh Odat; Fares Almomani (Energy Conversion and Management: X)
Space cooling now consumes about 20 % of global building electricity, using conventional vapor-compression cooling systems that are mainly powered by fossil-fuel electricity, thereby driving peak-power demand and greenhouse-gas emissions. This study numerically investigates a novel hybrid building-integrated solar chimney with an evaporative cooling tower (BISCECT) for sustainable space cooling and natural air ventilation. A model was developed using MATLAB/Simulink® software based on thermodynamic/ heat transfer equations. A comprehensive 9E assessment, encompassing energy, exergy, economic, environmental, energoeconomic, exergoeconomic, enviroeconomic, exergoenvironmental, and exergoenviroeconomic indicators, is carried out, alongside a sensitivity analysis of vapor-inlet temperature, chimney heat output, and geometric parameters. The simulation results indicated that the BISCECT system can supply 10 kW of thermal power with energy and exergy efficiencies of 32.19 % and 5.84 %, respectively. Moreover, the design achieves the levelized capital and operating costs of 89.01 $/kWh and 24.5 $/kWh, yielding a levelized cost of energy of 0.1137 $/kWh, while mitigating 4.58 t CO2 yr1 and realizing a two-year carbon payback period. These results demonstrate the thermo-enviro-economic viability of the proposed passive cooling concept for green residential buildings in hot-arid climates.